The Effects of Ability, Emotional Intelligence, and Professionalism on Employee Performance at the Regional Secretariat of Malang City - Arifin, Syaiful (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study aims to analyze the influence of ability, emotional intelligence, and professionalism on employee performance at the Malang City Regional Secretariat. In an increasingly dynamic work environment, these factors are important to ensure optimal performance improvement. The number of samples in this study was 141 employees, and the sampling technique used was a census. This research method uses a quantitative approach with multiple regression analysis, where data is obtained through a survey distributed to employees in the Malang City Regional Secretariat environment. The results of the study indicate that ability affects employee performance. Employees with higher abilities tend to be able to carry out tasks more efficiently and effectively, resulting in more optimal work output. Emotional intelligence has a significant effect on employee performance. High emotional intelligence helps employees maintain a harmonious work atmosphere and respond to situations calmly. The results of this study indicate that employees who have higher emotional intelligence are able to work more productively and collaboratively, which has a significant impact on their performance. Professionalism has a significant effect on employee performance. Employees who are professionals tend to work responsibly and maintain quality standards, thus supporting the success of the task. This professionalism creates a good and sustainable work culture, which encourages long-term employee performance improvement. Overall, these three variables contribute positively to improving employee performance.